2012
DOI: 10.7863/jum.2012.31.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Congenital Heart Disease by Early and Second-Trimester Fetal Echocardiography

Abstract: First-trimester echocardiography is feasible and seems to allow considerably earlier detection of major congenital heart disease. However, it should be kept in mind that although most forms of heart defects can be diagnosed early in pregnancy, some may develop and become apparent only later in gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 20 publications
(24 reference statements)
1
60
1
2
Order By: Relevance
“…Other studies have also looked at the usefulness of evaluation of the fetal heart early in gestation. [17][18][19] These studies demonstrated that early imaging of the fetal heart is technically feasible and can identify a wide spectrum of significant CHD; however, unlike our study, there was significant cardiac disease that was missed on the initial early evaluation. Of course, it is expected that not all CHD will be identified, though we believe that with increasing experience and fetal cardiac expertise, improvements in technology, and creation of universal guidelines for fetal cardiac imaging, detection rates and accuracy will continue to improve.…”
Section: Discussioncontrasting
confidence: 45%
“…Other studies have also looked at the usefulness of evaluation of the fetal heart early in gestation. [17][18][19] These studies demonstrated that early imaging of the fetal heart is technically feasible and can identify a wide spectrum of significant CHD; however, unlike our study, there was significant cardiac disease that was missed on the initial early evaluation. Of course, it is expected that not all CHD will be identified, though we believe that with increasing experience and fetal cardiac expertise, improvements in technology, and creation of universal guidelines for fetal cardiac imaging, detection rates and accuracy will continue to improve.…”
Section: Discussioncontrasting
confidence: 45%
“…The technical limits of EFEC are CRL < 50 mm, an increase of maternal Body mass index (BMI), unfavorable fetal position and a possible progression of cardiac disease especially in outflow obstructions [12,13]. This means that the pregnant women should be informed about the limits of early screening and also recommended to have a further scan as from 18 weeks for a more complete diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal cardiac ultrasound analysis performed between the 12th and 16th week of pregnancy (compared with the usual 18-22 weeks) is defined as Early Fetal Echocardiography (EFEC) [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal screening for anatomical and functional congenital heart disease (CHD) by fetal ultrasound and echocardiography allows the early prenatal diagnosis and postnatal prognosis by allowing the planning of delivery, and in some cases, the administration of prenatal therapy [1]. A detailed assessment of cardiac function by echocardiography is routinely performed in fetuses with CHD, and, recently, in those without anatomical heart defects, because it can assist in prenatal management and predict the perinatal and cardiovascular risks in the long term.…”
Section: Introductionmentioning
confidence: 99%